Low Oxygen Levels Induce Early Luteinization Associated Changes in Bovine Granulosa Cells - Baddela, Vijay S.; Sharma, Arpna; Viergutz, Torsten; Koczan, Dirk; Vanselow, Jens (Frontiers in Physiology, 2018)
During follicle maturation, oxygen levels continuously decrease in the follicular fluid and reach lowest levels in the preovulatory follicle. The current study was designed to comprehensively understand effects of low oxygen levels on bovine granulosa cells (GC) using our established estrogen active GC culture model. As evident from flow cytometry analysis the viability of GC was not found to be affected at severely low oxygen condition (1% O2) compared to normal (atmospheric) oxygen condition (21% O2). Estimations of hormone concentrations using competitive radioimmunoassay revealed that the production of estradiol and progesterone was significantly reduced at low oxygen condition. To understand the genome-wide changes of gene expression, mRNA microarray analysis was performed using Affymetrix’s Bovine Gene 1.0 ST Arrays. This resulted in the identification of 1104 differentially regulated genes of which 505 were up- and 599 down-regulated under low oxygen conditions. Pathway analysis using Ingenuity pathway analyzer (IPA) identified 36 significantly affected (p < 0.05) canonical pathways. Importantly, pathways like “Estrogen-mediated S-phase Entry” and “Cyclins and Cell Cycle Regulation” were found to be greatly down-regulated at low oxygen levels. This was experimentally validated using flow cytometry based cell cycle analysis. Up-regulation of critical genes associated with angiogenesis, inflammation, and glucose metabolism, and down-regulation of FSH signaling, steroidogenesis and cell proliferation indicated that low oxygen levels induced early luteinization associated changes in granulosa cells. Identification of unmethylated CpG sites in the CYP19A1 promoter region suggests that granulosa cells were not completely transformed into luteal cells under the present low oxygen in vitro condition. In addition, the comparison with earlier published in vivo microarray data indicated that 1107 genes showed a similar expression pattern in granulosa cells at low oxygen levels (in vitro) as found in preovulatory follicles after the LH surge (in vivo). Overall, our findings demonstrate for the first time that low oxygen levels in preovulatory follicles may play an important role in supporting early events of luteinization in granulosa cells.